2017
DOI: 10.1007/s11947-017-1995-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Barrier, and Antioxidant Properties of Pea Starch-Guar Gum Biocomposite Edible Films by Incorporation of Natural Plant Extracts

Abstract: Active food packaging based on pea starch and guar gum (PSGG) films containing natural antioxidants (NAs) was developed. Four kinds of NAs (epigallocatechin gallate (EGCG), blueberry ash (BBA) fruit extract, macadamia (MAC) peel extract, and banana (BAN) peel extract) were added into PSGG-based films as antioxidant additive. The effects of these compounds at different amounts on physical and antioxidant characteristics of PSGG film were investigated. The antioxidant activity was calculated with three analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 75 publications
0
23
1
Order By: Relevance
“…The values of TPC and antioxidant activities, including DPPH, ABTS, and FRAP, among the rice noodle samples (as shown in Table ) were not significantly different ( p > 0.05). Even though some reports have revealed that hydroclloid hydroxyl groups are able to interact with phenolic compounds by hydrogen bonding, which may be a result of TPC and antioxidant activity reductions, the results of the present study show that small amounts of gums (0.2% and 0.4%) used had no effect on these properties ( p > 0.05). Soultani et al found that an addition of pectin (0.5% and 1%) had no effect on the antioxidant capacity (FRAP) and phenolic content of black, green, mountain tea, and Pelargonium purpureum .…”
Section: Resultscontrasting
confidence: 94%
“…The values of TPC and antioxidant activities, including DPPH, ABTS, and FRAP, among the rice noodle samples (as shown in Table ) were not significantly different ( p > 0.05). Even though some reports have revealed that hydroclloid hydroxyl groups are able to interact with phenolic compounds by hydrogen bonding, which may be a result of TPC and antioxidant activity reductions, the results of the present study show that small amounts of gums (0.2% and 0.4%) used had no effect on these properties ( p > 0.05). Soultani et al found that an addition of pectin (0.5% and 1%) had no effect on the antioxidant capacity (FRAP) and phenolic content of black, green, mountain tea, and Pelargonium purpureum .…”
Section: Resultscontrasting
confidence: 94%
“…Vilas et al (2018) reported a tri-phasic edible film from GG loaded with plant-based antimicrobial compounds [21]. Saberi et al (2017aSaberi et al ( , 2017b presented an edible pea starch-GG biocomposite edible film as an antimicrobial agent for active food packaging [22,23]. Dhumal et al (2019aDhumal et al ( , 2019b reported that GG films with essential oils as active packaging materials have the potential to function as antimicrobial agents [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in food, chemical, textile and building materials industries, and is also one of the most promising materials for applications in food packaging (Piñeros-Hernandez, Medina-Jaramillo, López-Córdoba, & Goyanes, 2017;Saberi et al, 2016). As a potential alternative to conventional plastics, several novel bio-based materials have been investigated from corn (Li et al, 2018), wheat (Song, Zuo, & Chen, 2018), cassava (Edhirej, Sapuan, Jawaid, & Zahari, 2017), potato (Malmir et al, 2018), pea (Saberi et al, 2017), and sugar palm starch ( (Jumaidin, Sapuan, Jawaid, Ishak, & Sahari, 2016;Sahari, Sapuan, Zainudin, & Maleque, 2013;Sanyang, Sapuan, Jawaid, Ishak, & Sahari, 2015). Cornstarch (CS) has attracted exclusive attention for the preparation of biodegradable films because of its low cost and the largest source .…”
Section: Introductionmentioning
confidence: 99%